Healthcare or sickcare: reestablishing the balance - Julio Frenk; Octavio Gómez-Dantés (Salud Pública de México, 2016)
In this essay we discuss the need to reestablish the balance between health enhancing activities and care for the sick in order to meet the challenges of the 21st century.We first briefly review the historical evolution of personal and public hygiene.We then discuss the increasing emphasis on curative care that has characterized the modern world. We conclude that,in orderto meet the emerging challenges,contemporary health systems need to adopt a comprehensive scope which include upstream interventions to address the determinants of health; public health interventions to deal with major risk factors; personal health services to manage common infections, reproductive problems, non-communicable diseases, injuries, and mental health problems; and palliative care to deal with old age and the final phases of the human life cycle.